Leni : the life and work of Leni Riefenstahl - Bach, Steven (A Borzoi book, 2007)
Leni Riefenstahl, the woman best known as "Hitler's filmmaker," is one of the most controversial personalities of the twentieth century. Her story is one of huge talent and huger ambition, one that probes the sometimes blurred borders dividing art and beauty from truth and humanity. Two of her films, Olympia and Triumph of the Will, are universally regarded as among the greatest and most innovative documentaries ever made, but they are also insidious glorifications of Hitler and the Third Reich. Relying on new sources--including interviews with her colleagues and intimate friends, as well as on previously unknown recordings of Riefenstahl herself--biographer Bach untangles the truths and lies behind this gifted woman's lifelong self-vindication as an apolitical artist who claimed she knew nothing of the Holocaust and denied her complicity with the criminal regime she both used and sanctified.--From publisher description